Inter-Vehicle Communication at Intersections : An Evaluation of Ad-Hoc and Cellular Communication - Mangel, Thomas (KIT Scientific Publishing, 2012)
This book evaluates the ability of ad-hoc and cellular communication to enable cross-traffic assistance at intersections. Potential issues like Non-Line-Of-Sight (NLOS) reception with ad-hoc and limited capacity, higher latency and costs with cellular technology are investigated in two individual evaluations. A method for efficient information delivery via cellular systems and an inter-vehicle NLOS radio propagation model are proposed. Finally, the suitability of both technologies is compared.